Gradient composite material bar containing high-density crimped metal fibers and preparation method

By using the gradient composite rod containing high-density curled metal fibers in the material, the laser selection melting, rotary forging and surface mechanical grinding, the problems of difficult to lighten the materials and lower plastic toughness in the prior art are solved, and the high strength, high toughness and lightweight performance of the material are achieved.

CN119839091AActive Publication Date: 2025-04-18NANJING UNIV OF SCI & TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411919343.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-18
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve lightweighting of the material while ensuring the strength and performance of the material, and the plastic toughness of the material is difficult to maintain during the violent plastic deformation.

Method used

A gradient composite rod containing high-density curled metal fibers is prepared by laser selection melting, rotary forging and mechanical surface grinding to form a complex and orderly fiber system to improve the strength and fracture resistance of the material.

Benefits of technology

The ultimate tensile strength and yield strength of the material are significantly improved, while maintaining high plastic toughness and reducing structural weight while ensuring strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839091A_ABST
    Figure CN119839091A_ABST
Patent Text Reader

Abstract

The invention relates to a gradient composite material bar containing high-density crimped metal fibers and a preparation method of the gradient composite material bar. Comprising the following steps: (1) preparing curled metal fibers by adopting selective laser melting; (2) preparing a curled metal fiber bundle; (3) putting the metal fiber bundle into a pouring mold, and pouring an aluminum alloy solution to obtain an alloy bar containing curled metal fibers; (4) the alloy bar is heated, subjected to heat preservation and then subjected to rotary forging and pressing, and a lengthened composite bar is obtained; and (5) mechanically grinding the surface of the elongated composite bar to obtain the gradient composite bar containing the high-density crimped metal fibers, wherein the surface of the gradient composite bar is a fine grain layer, and the core part of the gradient composite bar is coarse grains. According to the method, selective laser melting and hot rotary swaging are combined, the bar with a heterostructure is obtained, the strength of the alloy bar is remarkably improved, the plasticity is reserved, and meanwhile the fracture resistance of the bar or a cable can be improved through the high-density curled metal fibers contained in the bar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a gradient composite material rod containing high-density curled metal fibers and a preparation method thereof. Background Art

[0002] Ti6Al4V (TC4) titanium alloy is one of the materials that has attracted much attention and developed rapidly at home and abroad. It is also a material that is widely used in the aerospace field. It is a typical α+β type titanium alloy with good comprehensive properties. It is the largest alloy used in titanium alloys and is favored by the aerospace field, the navigation field, and the defense military field. TC4 titanium alloy is often used to manufacture various precision parts required for aircraft, such as the fixing plate of the aircraft tail and the rotor blade bracket of the Black Hawk helicopter. Both experiments and practical applications have shown that parts made of titanium alloys can increase the service life of the device and significantly improve its fatigue limit.

[0003] Selective laser melting (SLM) is a powder bed melting technology in additive manufacturing. It has been used to prepare complex and fine structures and can solve the problems that arise in the casting and forging processes of titanium alloys. This technology mainly uses a high-energy laser to melt a thin layer of powder based on the computer-aided design model of the part to be processed, and forms high-density parts of any shape by layer-by-layer powder laying, melting and accumulating. Due to its unique advantages in manufacturing complex and precise structures, SLM technology has shown great application potential in the aerospace field.

[0004] The 7××× series aluminum alloy based on the Al-Zn-Mg-Cu element system is a precipitation hardening type of deformed aluminum alloy with high specific strength, good formability, excellent thermal conductivity and corrosion resistance. As a high-strength aluminum alloy, the 7××× series aluminum alloy has shown unique advantages in the fields of aerospace, automobile industry and national defense and military industry. In the field of aerospace, the 7××× series aluminum alloy is mainly used to manufacture aircraft structures, wings, fuselages and engine parts; in the field of automobile manufacturing, it is widely used in automobile parts, such as engine housings, wheels, etc.; in the field of national defense and military industry, it is mainly used to manufacture structural components of military equipment such as rockets and missiles. In order to further improve the comprehensive performance of the 7××× series aluminum alloy, we can use severe plastic deformation (SPD) technology to prepare ultrafine-grained materials. It is currently recognized as the most effective, most promising and most widely used method for preparing ultrafine-grained materials. SPD mainly applies single or multiple shear strains to the material to break and refine the grains inside the material and increase the defect density, thereby improving the performance of the material from all aspects. As people continue to explore SPD, many SPD processes have been developed one after another. Common severe plastic deformation processing methods include equal channel extrusion, high pressure torsion, torsion extrusion, cyclic expansion extrusion, simple shear extrusion, multi-directional forging, cumulative rolling and deep cold rolling, deep cold asynchronous rolling, etc. These processing methods, under certain temperature and strain rate conditions, overcome the deformation resistance of the metal by applying various forms of external force, causing it to produce severe plastic deformation, thereby obtaining the required aluminum alloy profiles of various shapes, specifications, sizes and organizational properties, and their strength is greatly improved, but the plastic toughness is reduced. Tang et al. adopted the process of solid solution (475℃ / 2h) + ECAP (300℃ / 16 passes) + room temperature cold rolling + aging at 110℃ for 22h, and finally increased the yield strength and tensile strength of Al-Zn-Mg-Sc-Zr alloy from 456MPa and 469MPa to 594MPa and 606MPa, but the elongation dropped from 16.7% to 10%. Although its tensile strength increased by 30.3% and its yield strength increased by 29.2%, its elongation decreased; Wang et al. studied 1060 aluminum alloy and found that under low-temperature cumulative rolling conditions, with the increase of rolling passes, the tensile strength and yield strength of the material increased rapidly from the annealing state to the first rolling pass, but the elongation decreased significantly. Summary of the invention

[0005] The purpose of the present invention is to provide a gradient composite material rod containing high-density curled metal fibers and a preparation method thereof. Since the rod contains high-density curled metal fibers, they are intertwined and distributed with each other to form a complex and ordered fiber system. Even if tiny cracks appear in some fibers, the adjacent curled fibers can prevent the cracks from extending further. At the same time, it can achieve a significant improvement in the ultimate tensile strength and yield strength of the metal material at the expense of a smaller elongation, but without a significant decrease in plastic toughness.

[0006] The technical solution to achieve the purpose of the present invention is: a method for preparing a gradient composite material rod containing high-density curled metal fibers, comprising the following steps:

[0007] Step (1): using alloy powder with a melting point higher than 800° C. as raw material and adopting laser selective melting to prepare a plurality of curled metal fibers;

[0008] Step (2): twisting a plurality of curled metal fibers to obtain a loose curled metal fiber bundle;

[0009] Step (3): melting the aluminum alloy into a liquid state, placing the curled metal fiber bundle into a casting mold, pouring the aluminum alloy solution, and obtaining an alloy rod containing the curled metal fibers;

[0010] Step (4): heating and keeping the alloy rod in step (3) and then performing rotary forging to obtain an elongated composite rod;

[0011] Step (5): The elongated composite rod obtained in step (4) is subjected to surface mechanical grinding to obtain a gradient composite material rod having a fine-grained surface layer and a coarse-grained core and containing high-density curled metal fibers.

[0012] Furthermore, step (1) specifically includes the following steps:

[0013] Step (11): using TC4 alloy powder with a particle size range of 15-53 μm as a raw material;

[0014] Step (12): constructing a three-dimensional model of the curled metal fiber, placing the axial direction of the metal fiber perpendicular to the Z axis of the printing platform, slicing the three-dimensional model of the curled metal fiber to generate a metal fiber printing path; selecting a tree-shaped support structure according to the size and shape of the suspended area of ​​the curled metal fiber, adding it to the suspended part of the three-dimensional model of the curled metal fiber, and generating a support path;

[0015] Step (13): Setting printing parameters and performing laser selective melting printing to obtain curled metal fibers with a diameter of 0.5 mm to 1 mm.

[0016] Furthermore, in step (12), the thickness of the powder layer is set to 0.02 mm, and the three-dimensional model of the curled metal fiber is sliced ​​according to the thickness of the powder layer to generate a metal fiber printing path;

[0017] In step (12), the branch angle of the tree-shaped support structure is 30°-60°, and the branch spacing is 0.5 mm-1 mm;

[0018] The specific printing parameters of step (13) are:

[0019] The laser power is 300±10W, the scanning speed is 800mm / s-1200mm / s, the scanning spacing is 0.1±0.01mm, the spot diameter is 0.2±0.02mm, the substrate temperature is 100±5℃, and the printing process is protected by argon atmosphere.

[0020] Furthermore, the powder is austenitic stainless steel powder or ferritic stainless steel powder.

[0021] Furthermore, step (2) is specifically as follows: manually twisting the fiber by clamping one end of a curled metal fiber with tweezers or pliers, taking another metal fiber, crossing one end of the other metal fiber with one end of the first metal fiber, and rotating the tweezers or pliers to make the two metal fibers entangled with each other to form a twisted fiber bundle; repeating the above steps, adding more metal fibers, and continuously twisting until the desired high-density fiber bundle is achieved.

[0022] Furthermore, step (3) is specifically as follows: using 7055 aluminum alloy, casting at 680°C to 720°C, with a delay time of 5±0.5s, and casting into aluminum alloy-titanium alloy composite rods, the diameter of the cast rods being 8±1mm.

[0023] Furthermore, the aluminum alloy and titanium alloy curled metal fiber bundles are combined by using molten drop composite arc additive instead of casting in step (3).

[0024] Furthermore, step (4) is specifically as follows: heating and keeping the aluminum alloy-titanium alloy composite rod of step (3) warm, the heating temperature is 70% of the melting point of 7055 aluminum alloy, the keeping time is 10±1min, and after keeping warm, performing rotary forging with a diameter pressing amount of 1%-3% per pass and a total deformation amount of 10-20% to obtain an elongated composite rod.

[0025] Furthermore, in step (5), the surface mechanical grinding adopts a pressing head with a ball, the grinding speed is 0.1m / s-0.3m / s, the reduction amount of each pass is 5μm-50μm, and the total reduction amount is 25μm-250μm, and finally a gradient composite material rod with a fine-grained surface layer and a coarse-grained core containing high-density curled metal fibers is obtained.

[0026] A gradient composite material rod containing high-density curled metal fibers is prepared by the above method.

[0027] Compared with the prior art, the present invention has the following significant advantages:

[0028] (1) The present invention has a built-in high-density curled metal fiber bundle. The metal fiber itself has high strength. After a large number of metal fibers are gathered into a high-density fiber bundle, the fibers support and cooperate with each other, so that the strength of the overall structure is further improved; in application scenarios that need to withstand large tension, pressure or impact force, the high-density curled metal fiber bundle can maintain the stability and integrity of the structure; when the material produces defects such as cracks during severe plastic deformation, the presence of high-density curled metal fibers can change the path of crack propagation; when the crack propagates in the composite material, it will deflect, branch, etc. when encountering the fiber, consuming more energy, thereby improving the toughness of the material.

[0029] (2) The use of composite materials of aluminum alloy and high-density curled titanium alloy metal fibers can reduce the weight of the structure while ensuring strength and performance; compared with traditional solid aluminum alloy materials, this composite material has a higher strength-to-weight ratio, thereby better achieving material lightweighting.

[0030] (3) Hot rotary forging of the aluminum alloy-titanium alloy composite rod in step (3) can further reduce the pores generated during the casting process and reduce its porosity; hot rotary forging can make the interface of the two alloys more tightly bonded, improve the bonding strength of the interface, and thus improve the overall performance of the composite material; during the hot rotary forging process, the material is subjected to strong plastic deformation at high temperature, so that the grains are refined; the refined grains can improve the strength, toughness and plasticity of the material. In terms of strength, the fine-grained material has more grain boundaries, which can hinder the movement of dislocations, thereby improving the strength of the material. In terms of toughness, the crack propagation path of the fine-grained material is more tortuous and requires more energy, so it has better toughness; at the same time, hot rotary forging can accurately control the size and shape of the material; by adjusting the rotary forging process parameters, a composite rod with high-precision dimensions can be obtained to meet the needs of different application fields.

[0031] (4) The present invention adopts surface mechanical grinding technology to prepare gradient composite material rods containing high-density curled metal fibers, and can obtain heterogeneous alloys with excellent inner and outer layer bonding; wherein, the outer layer of the rod presents an ultrafine grain structure, and the inner layer is a coarse grain elongated along the axial direction, thereby realizing the high strength and high toughness of the gradient fiber heterogeneous metal rod; at the same time, surface nano-sizing can adjust the ratio of the inner and outer layers of the conductor by changing the inner and outer radii, thereby adjusting the strength and plasticity matching of the high-strength and high-toughness alloy.

[0032] (5) The processing technology involved in the present invention is mature, the experimental equipment is complete, the investment cost is low, it is safe and environmentally friendly, the production efficiency is high, and it is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the laser selective melting process in the present invention, wherein (a) is a schematic diagram of the laser selective melting equipment printing titanium alloy curled metal fibers; (b) is a schematic diagram of the curled metal fiber bundle.

[0034] Figure 2 Schematic diagram of pouring aluminum liquid, where (a) is a casting schematic diagram, and (b) is a composite material rod containing curled metal fibers obtained by casting.

[0035] Figure 3 Schematic diagram of hot rotary forging; (a) is a schematic diagram of hot rotary forging, and (b) is a composite material rod obtained by hot rotary forging.

[0036] Figure 4 Schematic diagram of the processing of gradient composite rods containing high-density curled metal fibers using surface nano-processing.

[0037] Figure 5 Schematic diagram of the cross section of the gradient structure composite rod of the present invention, wherein (a) is a cross section of the composite rod elongated after hot rotary forging, and (b) is a cross section of the composite rod after surface nano-crystallization. DETAILED DESCRIPTION

[0038] The specific implementation modes of the present invention are further described in detail below, but the implementation modes of the present invention are not limited thereto.

[0039] The present invention provides a gradient composite material rod containing high-density curled metal fibers and a preparation method thereof. The specific scheme is as follows:

[0040] The present invention combines laser selective melting technology, casting technology, hot rotary forging technology and surface mechanical grinding technology to finally obtain a gradient composite material rod containing high-density curled metal fibers with a fine-grained surface layer and a coarse-grained core, comprising the following steps:

[0041] Prepare TC4 titanium alloy powder as raw material, use a vacuum drying oven to dry the titanium alloy powder, set the temperature to 80℃-180℃, dry for 2h, and then take it out after vacuum cooling for 2h.

[0042] Use 3D modeling software on the computer to design the required overall 3D solid model of the curled metal fiber with a diameter of 0.5mm-1mm, convert the 3D model file into stl format, rotate the model in the slicing software, place the axial direction of the metal fiber perpendicular to the Z axis of the printing platform, set the powder layer thickness to 0.02mm, and let the slicing software slice the model according to the set layer thickness to generate a printing path; select a suitable support structure according to the size and shape of the suspended area, select tree-shaped support, set the branch angle to 30°-60°, and the branch spacing to 0.5mm-1mm, and add the selected support structure to the suspended part of the model in the software.

[0043] A titanium alloy substrate was selected and fixed on a liftable workbench in the SLM equipment. The SLM equipment was then leveled. The dried titanium alloy powder was then thinly and evenly spread on the powder feeding platform. The SLM equipment was evacuated and filled with argon gas for atmosphere protection. Laser selective melting was then performed with the following process parameters: laser power of 300W, scanning speed of 800mm / s-1200mm / s, scanning spacing of 0.1mm, spot diameter of 0.2mm, substrate temperature of 100℃, and argon atmosphere protection was used during the printing process. The diameter of the curled metal fiber was 0.5mm-1mm. The horizontal scraper first evenly spreads a thin layer of metal powder on the substrate. The high-energy laser beam selectively melts the powder on the substrate according to the data of the current layer of the three-dimensional digital model to form the shape of the current layer of the part. Then the horizontal scraper spreads another layer of metal powder on the processed layer. The high-energy laser beam selectively melts according to the data of the next layer of the digital model. After each layer of the laid forming material is melted, the working platform is lowered by one layer thickness, and then the forming material is flattened on the working platform, and the selective melting is continued. The selective melting is cyclically performed until it is gradually accumulated to obtain a number of curly metal fibers with a diameter of 0.5mm-1mm, such as Figure 1 (a) shown.

[0044] Twist several curled metal fibers together, hold one end of a metal fiber with fine tweezers or small pliers, select another metal fiber, cross one end of it with one end of the first metal fiber, and slowly rotate the tweezers or pliers to make the two metal fibers entangle with each other, gradually forming a twisted fiber bundle. Repeat the above steps, add more metal fibers, and continue to twist to obtain a loose curled metal fiber bundle, such as Figure 1 (b) as shown.

[0045] The present invention provides a set of casting molds, and puts the curled metal fiber bundle into the casting mold; smelts the 7055 aluminum alloy at a melting temperature of 700°C, and melts the aluminum or aluminum alloy through an electromagnetic induction heating furnace. When the temperature of the alloy solution reaches 500°C, a refining agent is added to refine and remove slag from the alloy. After the step is completed, the heating frequency of the induction coil is adjusted to keep the aluminum alloy melt warm at the casting temperature, and wait for casting.

[0046] like Figure 2 As shown in (a), aluminum alloy solution is poured into a casting mold to cast, so that the aluminum alloy matrix and the curled metal fiber bundle are firmly combined, and an alloy rod containing curled metal fibers is obtained. The formed alloy rod is as shown in Figure 2 As shown in (b); the aluminum alloy casting is carried out at 680℃~720℃, with a delay time of 5s. After the casting is completed, it is cooled and then taken out from the casting mold. The diameter of the cast rod is about 8mm.

[0047] The obtained aluminum alloy-titanium alloy composite rod is heated and kept warm at a temperature of 70% of the melting point of the 7055 aluminum alloy for 10 minutes. After the heat preservation, the rotary forging is performed with a diameter reduction of 1%-3% per pass and a total deformation of 10-20%. The rotary forging schematic diagram is shown in FIG. Figure 3 As shown in (a), an elongated composite rod is obtained. The elongated composite rod is as shown in Figure 3 (b) shows that its internal grain structure is Figure 5 (a) shown.

[0048] like Figure 4 As shown, the surface of the elongated composite rod is mechanically ground, using a ball-bearing indenter, the grinding speed is 0.1m / s-0.3m / s, the reduction amount per pass is 5μm-50μm, and the total reduction amount is 25μm-250μm, and finally a gradient composite material rod with a fine-grained surface layer and a coarse-grained core containing high-density curled metal fibers is obtained. The internal grain structure is as shown in Figure 5 (b) as shown.

[0049] In summary, the gradient composite material rod containing high-density curled metal fibers prepared by the present invention has excellent performance and has a better match between strength and plasticity and toughness. At the same time, since the rod contains high-density curled metal fibers, they are intertwined and distributed with each other to form a complex and ordered fiber system, thereby further improving the strength and fracture resistance of the composite material rod.

Claims

1. A method for preparing a gradient composite material rod containing high-density curled metal fibers, characterized in that: The steps include: Step (1): using alloy powder with a melting point higher than 800° C. as raw material and adopting laser selective melting to prepare a plurality of curled metal fibers; Step (2): twisting a plurality of curled metal fibers to obtain a loose curled metal fiber bundle; Step (3): melting the aluminum alloy into a liquid state, placing the curled metal fiber bundle into a casting mold, pouring the aluminum alloy solution, and obtaining an alloy rod containing the curled metal fibers; Step (4): heating and keeping the alloy rod in step (3) and then performing rotary forging to obtain an elongated composite rod; Step (5): The elongated composite rod obtained in step (4) is subjected to surface mechanical grinding to obtain a gradient composite material rod having a fine-grained surface layer and a coarse-grained core and containing high-density curled metal fibers.

2. The method according to claim 1, characterized in that Step (1) specifically includes the following steps: Step (11): using TC4 alloy powder with a particle size range of 15-53 μm as a raw material; Step (12): constructing a three-dimensional model of the curled metal fiber, placing the axial direction of the metal fiber perpendicular to the Z axis of the printing platform, and slicing the three-dimensional model of the curled metal fiber to generate a metal fiber printing path; A tree-shaped support structure is selected according to the size and shape of the suspended area of ​​the curled metal fiber, and is added to the suspended part of the three-dimensional model of the curled metal fiber, and a support path is generated; Step (13): Setting printing parameters and performing laser selective melting printing to obtain curled metal fibers with a diameter of 0.5 mm to 1 mm.

3. The method according to claim 2, characterized in that In step (12), the powder layer thickness is set to 0.02 mm, and the three-dimensional model of the curled metal fiber is sliced ​​according to the powder layer thickness to generate a metal fiber printing path; In step (12), the branch angle of the tree-shaped support structure is 30°-60°, and the branch spacing is 0.5 mm-1 mm; The specific printing parameters of step (13) are: The laser power is 300±10W, the scanning speed is 800mm / s-1200mm / s, the scanning spacing is 0.1±0.01mm, the spot diameter is 0.2±0.02mm, the substrate temperature is 100±5℃, and the printing process is protected by argon atmosphere.

4. The method according to claim 1, characterized in that The powder is austenitic stainless steel powder or ferritic stainless steel powder.

5. The method according to claim 3, characterized in that: Step (2) is specifically as follows: manually twisting the fiber by clamping one end of a curled metal fiber with tweezers or pliers, taking another metal fiber, crossing one end of the other metal fiber with one end of the first metal fiber, and rotating the tweezers or pliers to make the two metal fibers entangled with each other to form a twisted fiber bundle; repeating the above steps, adding more metal fibers, and continuously twisting until the desired high-density fiber bundle is achieved.

6. The method according to claim 5, characterized in that Step (3) is specifically as follows: using 7055 aluminum alloy, casting at 680°C to 720°C, with a delay time of 5±0.5s, and casting to form aluminum alloy-titanium alloy composite rods, the diameter of the cast rods being 8±1mm.

7. The method according to claim 1, characterized in that The aluminum alloy and titanium alloy curled metal fiber bundles are combined by using molten drop composite arc additive instead of casting in step (3).

8. The method according to claim 6, characterized in that Step (4) is specifically as follows: heating and keeping the aluminum alloy-titanium alloy composite rod of step (3) at a heating temperature of 70% of the melting point of 7055 aluminum alloy for a holding time of 10±1 min, and after holding, performing rotary forging with a diameter reduction amount of 1%-3% per pass and a total deformation amount of 10-20% to obtain an elongated composite rod.

9. The method according to claim 8, characterized in that In step (5), the surface mechanical grinding uses a pressure head with a ball, the grinding speed is 0.1m / s-0.3m / s, the reduction amount per pass is 5μm-50μm, and the total reduction amount is 25μm-250μm, and finally a gradient composite material rod with a fine-grained surface layer and a coarse-grained core containing high-density curled metal fibers is obtained.

10. A gradient composite material rod containing high-density curled metal fibers, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • COMPOSITE OF ALUMINUM AND ALUMINA FIBERS AND MANUFACTURING THEREOF

    BE835435A

  • Abradable coating system

    CA2717827A1

  • Preparation method of high-strength porous three-dimensional ceramic-based metal composite material

    CN110983209A

  • 3D printing 3D network structure graphite / metal composite and normal-pressure casting infiltration preparation method thereof

    CN111761061A

  • Heterogeneous aluminum-magnesium alloy bar and preparation method thereof

    CN113843381A